HANDLING THE FINANCING PROBLEM: A NARRATIVE STUDY OF AGRICULTURAL CAPITAL FINANCING MURABAHAH CONTRACTS AT BMT - Joko Hadi Purnomo; Anike Putri Rahmawati; Niswatin Nurul Hidayat (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2021)
This research aims to determine how the implementation of agricultural capital financing with the murabahah contract, the factors that caused problematic financing, and how to handle problematic financing, especially in the financing of agricultural capital with a murabahah contract at BMT BUS KPU Tuban Branch. Agricultural capital financing is a type of financing that is quite rare for BMT in Tuban District, because in providing agricultural financing, BMT is very vulnerable to suffer losses due to problematic financing. This research was a field research with a qualitative approach. Data collection techniques were carried out through interviews and documentation. Data sources consists of primary and secondary data. Data analysis used analytic descriptive technique. The results explained that the murabahah financing procedure implemented at BMT BUS KPU Tuban Branch on agricultural capital financing practices can be said to be good, because in its implementation each prospective member of the financing was obliged to meet the applicable requirements and procedures, the factors that cause problematic financing were external and internal factors, The strategy for handling problematic financing at BMT BUS KPU Tuban Branch used a family approach, intensive billing, financing restructuring, collateral takeover, collateral execution and finally if it was not successful with financing elimination.